Thematic Learning Plan With A Nature Of Science Learning Model In The Fourth Grade Of Elementary School - Juni Pratama, I Gede Dendy; Dantes, Nyoman; Yudiana, Kadek (International Journal of Elementary Education, 2020)
The low student learning achievement is due to the thematic learning process that is not optimal. A valid and practical lesson plan is needed to realize a more meaningful learning process. This study aims to develop a thematic lesson plan with a scientific approach to the Nature Of Science learning model. The type of research used is research and development. The development model used in this research is the 4D development model. The subject of this research is the validity of learning tools in the form of lesson plans. This study's data collection method was to provide validity sheets to 2 experts and give practicality sheets to 5 practitioners. The instruments used were in the form of a validity sheet and a practicality sheet for the lesson plans. This study obtained the Rxy results for the whole item worth 1.00, the r-table with the number N = 5 at the 5% significance level was 0.878, and the practicality test results of the learning tools obtained an average score of 3.67. This research concludes that the lesson plans developed are declared valid and meet practicality requirements. This research's implication is that lesson plans that have been tested for their validity and practicality can be implemented in the learning process.